„Funny things of such an old lady” - The use of humour in Hungarian older TikTokers’ videos on ageing - Pauló, Edit; Gradwohl, Regina (Magyar Gerontológia, 2024)
Our presentation examines how TikTokers above the age of sixty in Hungary seek to refine representations of ageing online through humorous short videos. As the number of internet and, parallelly, TikTok users grow, it is important to focus on less visible groups, too.